Combination of everolimus with trastuzumab plus paclitaxel as first-line treatment for patients with HER2-positive advanced breast cancer (BOLERO-1): a phase 3, randomised, double-blind, multicentre trial - Hurvitz, Sara A; Andre, Fabrice; Jiang, Zefei; Shao, Zhimin; Mano, Max S; Neciosup, Silvia P; Tseng, Ling-Min; Zhang, Qingyuan; Shen, Kunwei; Liu, Donggeng; Dreosti, Lydia M; Burris, Howard A; et al. (The lancet oncology, 2015)
mTOR inhibition reverses trastuzumab resistance via the hyperactivated PIK/AKT/mTOR pathway due to PTEN loss, by sensitising PTEN-deficient tumours to trastuzumab. The BOLERO-1 study assessed the efficacy and safety of adding everolimus to trastuzumab and paclitaxel as first-line treatment for patients with HER2-positive advanced breast cancer. In this phase 3, randomised, double-blind trial, patients were enrolled across 141 sites in 28 countries. Eligible patients were aged 18 years or older, with locally assessed HER2-positive advanced breast cancer, with Eastern Cooperative Oncology Group (ECOG) performance status of 0–1, who had not received previous trastuzumab or chemotherapy for advanced breast cancer within 12 months of randomisation, had measurable disease as per Response Evaluation Criteria in Solid Tumors (RECIST) or bone lesions in the absence of measurable disease, without previous systemic treatment for advanced disease except endocrine therapy. Patients were randomly assigned (2:1) with an interactive voice and web response system to receive either 10 mg everolimus once a day orally or placebo plus weekly trastuzumab intravenously at 4 mg/kg loading dose on day 1 with subsequent weekly doses of 2 mg/kg of each 4 week cycle plus paclitaxel intravenously at a dose of 80 mg/m2 on days 1, 8, and 15 of each 4 week cycle. Randomisation was stratified according to previous use of trastuzumab and visceral metastasis. Patients and investigators were masked to the assigned treatments. Identity of experimental treatments was concealed by use of everolimus and placebo that were identical in packaging, labelling, appearance, and administration schedule. The two primary objectives were investigator-assessed progression-free survival in the full study population and in the subset of patients with hormone receptor-negative breast cancer at baseline; the latter was added during the course of the study, before unmasking based on new clinical and biological findings from other studies. All efficacy analyses were based on the intention-to-treat population. Enrolment for this trial is closed and results of the final progression-free survival analyses are presented here. This trial is registered with ClinicalTrials.gov, number NCT00876395. Between Sept 10, 2009, and Dec 16, 2012, 719 patients were randomly assigned to receive everolimus (n=480) or placebo (n=239). Median follow-up was 41·3 months (IQR 35·4–46·6). In the full population, median progression-free survival was 14·95 months (95% CI 14·55–17·91) with everolimus versus 14·49 months (12·29–17·08) with placebo (hazard ratio 0·89, 95% CI 0·73–1·08; p=0·1166). In the HR-negative subpopulation (n=311), median progression-free survival with everolimus was 20·27 months (95% CI 14·95–24·08) versus 13·08 months (10·05–16·56) with placebo (hazard ratio 0·66, 95% CI 0·48–0·91; p=0·0049); however, the protocol-specified significance threshold (p=0·0044) was not crossed. The most common adverse events with everolimus were stomatitis (314 [67%] of 472 patients in the everolimus group vs 77 [32%] of 238 patients in the placebo group), diarrhoea (267 [57%] vs 111 [47%] patients), and alopecia (221 [47%] vs 125 [53%]). The most frequently reported grade 3 or 4 adverse events in the everolimus group versus the placebo group were neutropenia (117 [25%] vs 35 [15%]), stomatitis (59 [13%] vs three [1%]), anaemia (46 [10%] vs six [3%]) and diarrhoea (43 [9%] vs 10 [4%]) On-treatment adverse event-related deaths were reported in 17 (4%) patients in the everolimus group and none in the placebo group. Although progression-free survival was not significantly different between groups in the full analysis population, the 7·2 months prolongation we noted with the addition of everolimus in the HR-negative, HER2-positive population warrants further investigation, even if it did not meet prespecified criteria for significance. The safety profile was generally consistent with what was previously reported in BOLERO-3. Proactive monitoring and early management of adverse events in patients given everolimus and chemotherapy is crucial. Novartis Pharmaceuticals.